A Randomized Clinical Trial Comparing the Standard Mcintosh Laryngoscope and the C-Mac D blade Video laryngoscope™ for Double Lumen Tube Insertion for One Lung Ventilation in Onco surgical Patients - Shah, Shagun Bhatia (Indian J Anaesth, 2016)
BACKGROUND AND AIMS: Several devices enabling double-lumen tube (DLT) placement for thoracic surgeries are available, but there are no studies for D-blade video laryngoscope-guided DLT insertion. We compared the CMac D-blade videolaryngoscope™ and the Macintosh laryngoscope for DLT endobronchial intubation using parameters of time and attempts required for intubation, glottic view, incidence of complications and haemodynamic changes. METHODS: Prospective, parallel group, randomised controlled clinical trial where sixty American Society of Anesthesiologists I and II patients aged 18-80 years scheduled for thoracic surgeries entailing DLT placement were randomly allocated in two groups based on the laryngoscopic device used for endobronchial intubation. Data were subjected to statistical analysis SPSS (version 17), the paired and Student's t-test for equality of means. Nominal categorical data between the groups were compared using Chi-squared test or Fisher's exact test as appropriate. P ˂ 0.05 was considered statistically significant. RESULTS: Time required for intubation was comparable (37.41 ± 18.80 s in Group-M and 32.27 ± 11.13 s in Group-D). Number of attempts and incidence of complications (trauma, DLT cuff rupture, oesophageal intubation) was greater in the Macintosh group, except malpositioning into the wrong bronchus (easily rectified fibre-optic bronchoscopically), which was greater with the D-blade. Greater haemodynamic changes were observed during Macintosh laryngoscopy. CONCLUSION: D-blade videolaryngoscope™ is a useful alternative to the standard Macintosh laryngoscope for routine DLT insertion.